Interacting ω(q) dark energy model with phase space analysis - Yerzhanov, Koblandy; Myrzakul, Shynaray; Kenzhalin, Duman; Khurshudyan, Martiros (Modern physics letters A, 2021)
The phase space analysis has been used to probe the accelerated expansion of the Universe when ω ( q ) dark energy interacts with cold dark matter. Non-gravitational interactions Q = 3 H b q ρ de and Q = 3 H b q ρ dm considered in this work are one of the first models of sign changing interactions that appeared in the literature. Specific ω ( q ) = ω 0 + ω 1 q dark energy model with P de = ω ( q ) ρ de has been assumed and all late time scaling attractors have been found. This is a two-parameter model with ω 0 and ω 1 parameters to be determined, while q is the deceleration parameter. In general the motivation to consider similar fluid models is directly related to the attempts to unify dark energy and dark matter involving the properties of the deceleration parameter. The previous study using similar dark energy model showed that the BOSS result for the expansion rate at z = 2 . 3 4 can be explained without interaction with cold dark matter. In this way, the previous result provides a reasonable basis to organize future studies in this direction. This study is one of the first attempts in this direction. It should be mentioned that the full comparison of the models with observation data and the classification of future singularities have been left as a subject of a forthcoming paper. There are several ways that the model can be extended which also has been left as a subject of a forthcoming paper.